Learning of bimodal vs. unimodal signals in restrained bumble bees (2020)
Similar to animal communication displays, flowers emit complex signals that attract pollinators. Signal complexity could lead to higher cognitive load for pollinators, impairing performance, or might benefit them by facilitating learning, memory and decision making. Here, we evaluated learning and memory in foragers of the bumble bee Bombus impatiens trained to simple (unimodal) versus complex (bimodal) signals under restrained conditions. Use of a proboscis extension response protocol enabled us to control the timing and duration of stimuli presented during absolute and differential learning tasks. Overall, we observed broad variation in performance under the two conditions, with bees trained to compound bimodal signals learning and remembering as well as, better than or more poorly than bees trained to unimodal signals. Interestingly, the outcome of training was affected by the specific colour-odour combination. Among unimodal stimuli, the performance with odour stimuli was higher than with colour stimuli, suggesting that olfactory signals played a more significant role in the compound bimodal condition. This was supported by the fact that after 24?h, most bimodal-treatment bees responded to odour but not visual stimuli. We did not observe differences in latency of response, suggesting that signal composition affected decision accuracy, not speed. We conclude that restrained bumble bee workers exhibit broad variation of responses to bimodal stimuli and that components of the bimodal signal may not be used equivalently. The analysis of bee performance under restrained conditions enables accurate control of the multimodal stimuli provided to individuals and to study the interaction of individual components within a compound.